Strategi Gereja Dalam Meningkatkan Perekonomian Jemaat Di Era Disrupsi - Rifa Idola Siregar; Jelita Harianja; Annesya Bagariang; Renny Victoria Sinaga; Oky Rasbina Karolina Br. Surbakti (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
In an era of disruption, the church needs to adapt to rapid social, technological and economic changes, the church as a religious institution also needs to adapt to face these challenges. One important aspect that needs to be considered is the congregation's economy. A strong and sustainable economy can provide support for church activities and the surrounding community. This research aims to identify effective church strategies in improving the congregation's economy in an era of disruption. Through a literature study approach and case studies of successful churches, several strategies were found that could be implemented: First, churches need to increase the congregation's skills and knowledge in facing economic changes. Second, churches need to utilize information and communication technology to support the congregation's economy. Third, the church can encourage entrepreneurship among the congregation. Support can be provided through providing co-working spaces in churches or establishing business incubators to help congregation members who want to start their own business. Churches can also facilitate business collaborations between congregations who have complementary skills and interests. Four, churches need to develop strategic partnerships with external parties, such as non-profit organizations, financial institutions, or private companies that have visions and values that are in line with the church. but must be based on the ethical and moral principles taught by religion.